Pengaruh Citra Merek Dan Brand Ambassador Korea Di Shopee Terhadap Minat Beli Mahasiswa Unsika - Permana, Vitho Bagus; Mardalena, Siahaan Trinita Tiodora; Sulaeman, Eman (Innovative: Journal Of Social Science Research, 2024)
This research was conducted to determine the impact of brand image and the utilization of Korean industry brand ambassadors on the purchase intention among students of Singaperbangsa Karawang University on the Shopee e-commerce platform. A descriptive quantitative approach was employed. The variables consisted of brand image perception and Korean brand ambassadors as independent variables, while purchase intention served as the dependent variable. The research utilized primary data from respondents via a Google Forms questionnaire, collecting responses from 150 Shopee-using student respondents through purposive random sampling. Data analysis involved validity and reliability testing, classical assumption testing, and multiple linear regression using SPSS software. The results revealed that brand image perception and Korean brand ambassadors significantly influenced purchase intentions, both partially and simultaneously, among the student population. The conclusion of this study states that Shopee needs to build a strong brand image and leverage the popularity of the Korean industry as a medium to foster consumer purchase intentions, particularly among students at the University of Singaperbangsa Karawang.